Monetary conflicts within co-residential unions: a comparative perspective - Kaittila Anniina (Research on Finnish Society & Turun korkeakoulujen yhteiskunnallistaloudellinen tutkimusyhdistys ry., 2022)
Although various studies indicate that money is a major source of conflict between cohabiting and marital partners, the existing research on what causes conflict within intimate relationships remains insufficient. Using data from the European Social Survey 2004/2005, this article explores the factors that predict monetary conflict between partners across 23 European countries. Previous research concerning financial conflicts has concentrated on individual level factors. This study adds a macro-level perspective to the existing body of research by exploring whether the rate of female labor force participation and societal gender equality are associated with the prevalence of conflict. Individual-level factors, such as personal characteristics, household controls, relative resources, and gender equality, explain the frequency of disagreements. At the macro-level, this study shows that relationship dynamics are affected by the institutional characteristics of countries. In particular, in countries where the rate of female labor force participation is high, conflicts over money are more common. However, societal gender equality does not explain the frequency of conflicts.